Temperature and Efficiency Analysis of Line Laser in Removing Tree Barriers for Overhead Lines - Xin XU; Chunhua FANG; Li ZHI; Can DING; Xiaohu DONG; Sheng CHENG; Wei SUN; Yuning TAO (Zhongguo dianli)
Overhead line tree barriers may cause line tripping faults and are a major hidden danger to line operation. It is a safe and effective way to remove the tree barriers under the transmission lines by high energy laser. By taking six types of typical trees as the research objects, finite element models are established to analyze the temperature distribution characteristics and burning efficiency of these trees under point and line laser cauterization, and point and line cauterization experiments are conducted respectively. The results show that the temperature of the tree surface decreases sharply from the the laser spot center to the spot edge, and the thermal effect is only obvious in the center of the burning area, and the temperature rising rate at the spot center slows down with the heating time. Within the same time period, compared to other five tree types, Paulownia has the highest temperature, reaching 1259.20 °C at maximum in 15 s. When the output power of laser is the same, the point laser and line laser have an average burning speed of 0.37 mm/s and 5.45 mm/s, respectively. The experimental results show that the line laser is 6.53-8.45 times faster than the point laser in average burning speed, which indicates that the line laser has a significantly higher burning speed than that of point laser. The research results can provide an important basis for application of line laser in clearing tree barriers.